The reciprocal relationship between non-alcoholic fatty liver disease and hypothyroidism: A systematic review and meta-analysis of about 39 million individuals - Ariyan Ayati Firoozabadi; Iman Elahi Vahed; Pouyan Lotfi; Adel Geshani; Ali Keshavarzian; Maryam Moftakhar; Mahkameh Razaghi; Zahra Rasouli; Mahtab Montazeri; Mohammad Ali Mansournia; Massoud Vosough; Mohammad Rahmanian (PLoS ONE, 2025)
Background Non-alcoholic fatty liver disease (NAFLD) and hypothyroidism are both prevalent conditions with potential reciprocal influences. This study evaluates the link between NAFLD and hypothyroidism. Methods A systematic search was performed using Scopus, PubMed, Web of Science, and Google Scholar. A random-effects meta-analysis assessed the bidirectional connection between hypothyroidism and NAFLD. Subgroup, meta-regression, and sensitivity analyses explored variability. R software (version 4.4.1) was employed for all analyses. Results Data from 38,877,762 people were assessed, with 99% being female, limiting generalizability to male populations. Among the study population, females were significantly more numerous than males. Hypothyroidism increased the presence of NAFLD and nonalcoholic steatohepatitis (NASH) (OR = 1.96, 95% CI = 1.34–2.87; I2 = 89%). In subgroup analysis, the incidence of NAFLD/NASH was increased in both subclinical and unspecified hypothyroidism patients (OR = 1.59, 95% CI = 1.08–2.35; I2 = 91%, and OR = 1.96, 95% CI = 1.09–3.54; I2 = 79%, respectively). Conversely, overt hypothyroidism did not significantly increase the risk of NAFLD/NASH (OR = 4.27, 95% CI = 0.90–20.19; I2 = 89%). Additionally, NAFLD patients were more likely to develop hypothyroidism (OR = 1.85, 95% CI = 1.35–2.53; I2 = 100%). According to the subgroup analysis, NAFLD patients were more prone to develop subclinical hypothyroidism (OR = 1.83, 95% CI = 1.11–3.03; I2 = 87%). The increased presence of overt hypothyroidism wasn’t found to be significant in NAFLD patients (OR = 1.94, 95% CI = 0.73–5.18). Conclusion This study suggests a reciprocal connection between hypothyroidism and NAFLD, underscoring the need for integrated management strategies and additional research into the underlying mechanisms. The predominance of female participants, combined with high heterogeneity, limits the applicability of findings to broader populations.